Development of emotional sweating in the newborn infant. Issue 9 (September 1982) - Harpin, V A; Rutter, N
Abstract : Sweating from the palm and sole occurs independently of ambient temperature but is influenced by emotional factors. It thus provides a useful objective measure of emotional state. The development of this emotional sweating in the newborn was investigated by measuring palmar water loss and relating it to the infant's state of arousal. Although 433 individual measurements were made on 124 babies of gestational age 25 to 41 weeks and postnatal age 15 hours to 9 weeks. Palmar water loss was also recorded continuously in 22 infants undergoing heel prick for routine blood sampling. In babies of 37 weeks' gestation or more, there was a clear relationship between palmar water loss and arousal from the day of birth, and by the third week levels on vigorous crying were comparable with those of an anxious adult. Less mature babies did not show emotional sweating at birth; it was first seen at the equivalent of 36 to 37 weeks' gestation regardless of maturity. Continuous recordings confirmed the cross-sectional data and illustrated the abrupt nature of the response. Emotional sweating could be a useful tool for the assessment of emotional state of the newborn.